A unified approach for determining the strength of FRC beams subjected to torsion–Part II: Analytical modeling. (12th October 2021) - Facconi, Luca; Amin, Ali; Minelli, Fausto; Plizzari, Giovanni
Abstract: The addition of fibers to structural concrete is an accepted means in academia and practice to traverse tension across cracks. Several international codes of practice contain provisions, which allow a designer to rely on the fibers to resist flexure and shear. However, despite the wider community appreciating that the presence of fibers can significantly increase the capacity of reinforced concrete in resisting torsion, design guidelines are currently unavailable to the practicing engineer. As a result of minimum reinforcement requirements prescribed by codes to prevent excessive torsional cracking in reinforced concrete, a significant underutilization of the fibers is often encountered and this can lead to costly and exorbitant designs. In the accompanying paper, benchmark experimental data were presented on 18 large‐scale fiber‐reinforced concrete (FRC) members subjected to torsion, which clearly identified the beneficial effects of the fibers at all stages of loading. In this study, simplified and advanced mechanically consistent analytical models are developed within the so‐called level of approximation approach (within the framework of current Model Code) to describe the strength of FRC beams loaded in torsion.